2019
DOI: 10.1083/jcb.201812106
|View full text |Cite
|
Sign up to set email alerts
|

SNX3 drives maturation of Borrelia phagosomes by forming a hub for PI(3)P, Rab5a, and galectin-9

Abstract: The spirochete Borrelia burgdorferi, the causative agent of Lyme disease, is internalized by macrophages and processed in phagolysosomes. Phagosomal compaction, a crucial step in phagolysosome maturation, is driven by contact of Rab5a-positive vesicles with the phagosomal coat. We show that the sorting nexin SNX3 is transported with Rab5a vesicles and that its PX domain enables vesicle–phagosome contact by binding to PI(3)P in the phagosomal coat. Moreover, the C-terminal region of SNX3 recruits galectin-9, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 72 publications
3
28
0
Order By: Relevance
“…41 Moreover, it was shown in macrophages that SNX3 is transported with Rab5a positive vesicles towards Borrelia burgdorferi-containing phagosomes to promote maturation of these organelles and the spirochete compaction. 42 Also in macrophages, SNX5 plays an important role during macropinosome biogenesis controlling the uptake and processing of soluble exogenous antigens. 43 We still do not know whether the difference of phagosomal maturation observed in SNX17 KD DCs enhances or partially restores the phenotype of cross-presentation found in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…41 Moreover, it was shown in macrophages that SNX3 is transported with Rab5a positive vesicles towards Borrelia burgdorferi-containing phagosomes to promote maturation of these organelles and the spirochete compaction. 42 Also in macrophages, SNX5 plays an important role during macropinosome biogenesis controlling the uptake and processing of soluble exogenous antigens. 43 We still do not know whether the difference of phagosomal maturation observed in SNX17 KD DCs enhances or partially restores the phenotype of cross-presentation found in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction of the membrane surface area is likely due to the extrusion of membrane tubules, which could be observed frequently, especially at sites of curvature discontinuity [21,56]. Multiple proteins have been identified which play crucial roles in the regulation of this process, including RabGTPases, sorting nexin 3 (SNX3) and galectin-9 [60]. RabGTPases are regulators of vesicle trafficking and vesicle fusion with and fission from membranes [61]; sorting nexins are a family of proteins involved in intracellular trafficking and possess a phospholipid binding PX domain [62]; the galectin family is involved in carbohydrate binding on the cell surface, but also in the regulation of intracellular trafficking pathways [63].…”
Section: Compaction Of Borrelia In the Phagosomementioning
confidence: 99%
“…Initially, Borrelia are internalized in a Rab22a-positive phagosome, which is in turn fused with vesicles that are positive for both Rab5a and SNX3 (Figure 3). siRNA-mediated depletion of either of those proteins significantly decreased the proportion of compacted Borrelia [21,60]. Interestingly, these points of contact between phagosome and vesicles are especially found at sites of altered membrane curvature on the phagosomal membrane, which also constitute the sites of membrane tubule formation and abscission [18,21,60].…”
Section: Compaction Of Borrelia In the Phagosomementioning
confidence: 99%
See 1 more Smart Citation
“…Further work has demonstrated that apart from galectin-3 and galectin-8, other galectins, including galectin-1, galectin-4, and galectin-9, are targeted towards impaired endocytic vesicles [ 23 , 24 ]. Remarkably, the timing of galectin-recruitment seems to differ between distinct galectin variants.…”
Section: Galectins In Intracellular Vesicular Compartmentsmentioning
confidence: 99%